Pengaruh Entrepreneurial Intentions, Job Insecurity, terhadap Organization Culture yang dimediasi oleh Depression pada Mahasiswa yang Berwirausaha di Jakarta - Siti Nurhaliza Sefa Putri Pratama; Netania Emilisa; Ratu Vanya Nurin Fathi Zulyar; Nadyne Auryn Sabrina (Politeknik Bisnis Indonesia, 2024)
The aim of this research is to find out whether there is an influence of Entrepreneurial Intentions, Job Insecurity, on Organization Culture which is mediated by Depression in Entrepreneurial Students in Jakarta. This research design was carried out by hypothesis testing. The data used is cross sectional because it will only be conducted once in a certain period and the unit of analysis is individuals, namely students who are entrepreneurs in Jakarta. From the descriptive statistical results of Entrepreneurial Intentions, it shows that respondents feel the existence of Entrepreneurial Intentions when starting an entrepreneur. The results of hypothesis testing show that there is a significant negative influence between Entrepreneurial Intentions and Depression. The results of hypothesis testing show that there is no significant influence between Entrepreneurial Intentions and Organizational Culture. The results of hypothesis testing show that there is a significant positive influence between Job Insecurity and Depression. The results of hypothesis testing show that there is no significant positive influence between Job Insecurity and Organization Culture. The results of hypothesis testing show that there is a significant influence between Depression and Organization Culture. The results of hypothesis testing show that there is a significant influence between Entrepreneurial Intentions on Organization Culture, mediated by Depression. The results of hypothesis testing show that there is a significant influence between Job Insecurity on Organization Culture, mediated by Depression.